Penggunaan Cyber Notary Pada Akta Autentik dan Kekuatan Pembuktiannya Dalam Perspektif Undang-Undang Jabatan Notaris - Friko Rumadanu; Esther Masri; Otih Handayani (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2022)
Notaries are currently allowed to certify electronic documents. This authority is contained in Article 15 paragraph (3) of Law Number 2 of 2014 concerning the position of a notary. A part from ratifying the deed, a notary can also save files in the form of file. But not a few notaries are still reluctant to use technology to make and ratify a deed due to conflicts between articles both in the notary office law itself and with articles in other laws. This study aims to determine whether the deed that uses information technology has the strength of proof like an authentic deed and whether the electronic certification carried out by a notary is in line with the duties and positions of the notary. The research method used is the type of normative legal research conducted by reviewing library materials on secondary data using a legal approach and a conceptual approach. This study focuses on the deed of the extraordinary general meeting of Shareholders of PT. Lippo Karawaci Tbk which was conducted via video conference on October13 2021. There was disagreement from several shareholders over the certification which was carried out electronically because it was considered to be able to make the deed a private deed. In addition to the conflict between the articles, this is also due to the absence of implementing regulations regarding the making of deeds through information technology by a notary so that there is a need for a review of the relevant Laws and the making of special implementing regulations for cyber notaries.